Efek Terapi Murottal Al-Qur’an Terhadap Peningkatan Berat Badan Bayi Prematur (Studi Eksperimen Pada Bayi Prematur) Di RSUD Dr. Chasbullah Abdulmadjid Kota Bekasi Tahun 2018 - Dyah Maria Ulfah; Gita Permata Sari (UP3M AKPER-AKBID BHAKTI HUSADA CIKARANG, 2019)
Pre-term babies are the babies born between 28 – 37 weeks pregnancy. They are at risk of facing death 70 times higher than normal babies. It is caused by the difficulties in adapting with the life outside the uterus because the organs haven’t developed completely, for instance lung in respiratory system, heart in blood circulation (heart), bowel in digest system and absorption, and brain in central nervous system. Murottal Al Qur’an is one of complementary therapy using sensory stimulation by listening Al Qur’an. The purpose of this research is to find out the effect of Murottal Al Qur’an therapy in gaining weight of pre-term babies with gender, gestational age, and weight variables. This research is quasi experiment with 15 respondents in controlled group and 15 respondents in intervention group. The collecting data is by weighing the pre-term babies and listening them to Al Qur’an Surah Ar-Rahman for 23 days. The result of bivariate with T-Independent test shows there is significance difference average weight between intervention group and controlled group with score ρ value (0,023) < α (0, 05). Based on the data, Ho is rejected which means there is an effect of Murottal therapy to pre-term babies’ weight in perinatology room in RSUD dr. Chasbullah Abdulmadjid Kota Bekasi.